The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5530/pj.2017.4.74
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Caco-2 and HeLa proliferation by Terminalia carpentariae C. T. White and Terminalia grandiflora Benth. extracts: Identification of triterpenoid components

Abstract: Background: Terminalia spp. are characterised by their high antioxidant capacities and many have anticancer activity. This study examines the anti-proliferative activity of T. carpentariae leaf and T. grandiflora leaf, fruit and nut extracts against Caco-2 and HeLa carcinoma proliferation. Materials and Methods: Powdered T. carpentariae leaf and T. grandiflora leaf, fruit and nut were extracted and tested for anti-proliferative activity against Caco-2 and HeLa cancer cell lines using colorimetric cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(62 reference statements)
1
1
0
Order By: Relevance
“…Our findings are consistent with reports showing antiproliferative and/or toxic effects of polyphenols or polyphenol rich extracts in Caco-2 cells and other cell lines, such as Courtney et al [41], Sánchez-Vioque et al [42] and Szewczyk et al [43] with Terminalia carpentariae and Terminalia grandiflora extracts, Oenothera paradoxa seed extract and Crocus sativus L. leaf extract, respectively. However, it is important to note that the authors reported concentrations between 0.5 to 1 mg mL −1 to exert a more potent inhibition of Caco-2 cell proliferation, which are 4-8 times higher compared to the highest concentration (0.125 mg mL −1 ) proved in this study.…”
Section: Effect In Caco-2 Cells Viabilitysupporting
confidence: 93%
“…Our findings are consistent with reports showing antiproliferative and/or toxic effects of polyphenols or polyphenol rich extracts in Caco-2 cells and other cell lines, such as Courtney et al [41], Sánchez-Vioque et al [42] and Szewczyk et al [43] with Terminalia carpentariae and Terminalia grandiflora extracts, Oenothera paradoxa seed extract and Crocus sativus L. leaf extract, respectively. However, it is important to note that the authors reported concentrations between 0.5 to 1 mg mL −1 to exert a more potent inhibition of Caco-2 cell proliferation, which are 4-8 times higher compared to the highest concentration (0.125 mg mL −1 ) proved in this study.…”
Section: Effect In Caco-2 Cells Viabilitysupporting
confidence: 93%
“…(T. carpentariae and T. grandiflora) were also recently reported to be good inhibitors of Caco2 and HeLa cell proliferation. 26 That study identified 3 lanostane and 2 pentacyclic triterpenoids in the extracts and postulated that they may contribute to this activity. Despite these previous studies, limited information is available on the anticancer activity of other Terminalia spp.…”
Section: Introductionmentioning
confidence: 99%